2010
DOI: 10.1007/s11033-010-0560-x
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis Δf508 mutation screening in Brazilian women with altered fertility

Abstract: Cystic Fibrosis (CF) is an autosomal recessive disease, caused by mutations in the Cystic Fibrosis Transmembrane Regulator gene (CFTR). The most frequent mutation in CF is ΔF508. The disease is clinically characterized by elevated concentrations of sweat chlorides and abnormally thick mucus. It affects organs such as lung, pancreas, gastrointestinal and reproductive tract. Women with CF commonly present delayed puberty and amenorrhea due to malnutrition. Our objective was to screen the presence of ΔF508 mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Furthermore, CFTR variants were more commonly detected in males compared with females, even though the difference did not reach statistical significance ( P = .46). The CF carrier status within our study was consistent with prior published reports of CF carrier prevalence on infertile male and females . The overall CF prevalence in our population is higher than the prevalence showed by Sugarman et al who found a 2.3% CFTR carrier frequency in Hispanic populations, although the population analyzed in that study consisted a broad U.S. based Hispanic residents and did not assess native Mexican Hispanics .…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, CFTR variants were more commonly detected in males compared with females, even though the difference did not reach statistical significance ( P = .46). The CF carrier status within our study was consistent with prior published reports of CF carrier prevalence on infertile male and females . The overall CF prevalence in our population is higher than the prevalence showed by Sugarman et al who found a 2.3% CFTR carrier frequency in Hispanic populations, although the population analyzed in that study consisted a broad U.S. based Hispanic residents and did not assess native Mexican Hispanics .…”
Section: Discussionsupporting
confidence: 91%
“…In 2011, Brunoro et al observed a higher percentage of CF carriers than expected among the 24 women with altered fertility in their study cohort (40). Another study in 2011 by Tomaiuolo et al showed an increased frequency of a specific CF mutation-the 5T haplotype-among women with tubal disease (32).…”
mentioning
confidence: 85%
“…Cystic fibrosis (CF) is an autosomal recessive disorder caused by various mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene, but the ΔF508 mutation (a deletion of the phenylalanine at amino acid position 508 in the protein) accounts for 70% of CF patients ( Kerem et al, 1989 ). Mutations in the CFTR gene encode a nonfunctional chloride channel, causing a broad range of deleterious effects ( Ramananda et al, 2024 ) including obstructive lung disease and increased susceptibility to respiratory infections ( Rowntree and Harris, 2003 ), pancreatic disorders ( Estivill et al, 1995 ), and reduced fertility in both males ( Alves et al, 2015 ) and females ( Brunoro et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%